Poisoning with e-cigarette liquid (VPG Power Smoke Baze) - case report - Zając, Marlena; Gruca, Dariusz; Wais, Marcin (Journal of Education, Health and Sport, 2023)
Introduction and purpose: E-cigarettes have emerged as an alternative to traditional tobacco smoking. Toxicological studies have investigated the composition and potential toxicity of e-cigarette liquid components. While they are generally considered less harmful than combustible cigarettes, cases of poisoning associated with e-cigarette liquid ingestion or exposure have been reported. Brief description of the state of knowledge: Nicotine intoxication resulting from e-cigarette liquid ingestion can lead to a range of symptoms and complications, including cardiovascular effects, neurological symptoms, gastrointestinal disturbances, respiratory issues, and even death. This report presents a case of a 58-year-old woman hospitalized in the Toxicology and Cardiology Department due to poisoning with e-cigarette liquid. Conclusions: Accidental or intentional ingestion and/or injection of e-liquid is becoming a new emerging challenge for Emergency Medicine, mainly because of the easy accessibility of advertisements and the sales of e-cigarettes online, and the high nicotine concentration in e-liquids. It is important to report instances of e-liquid-related nicotine intoxication in order to improve the legal restrictions on the sale of e-liquid.